Kinetics of Changes in Free Fatty Acids in Cassava Crackers (Kecimpring) Enriched with Catfish and Gotu Kola (Centella asiatica) Leaves During Storage - Muhammad Rifqi; Irma Siti Marhamah; Faridah Handayasari; Siti Nurhalimah (Universitas Djuanda, 2025)
Cassava crackers, also known as kecimpring, are a traditional Indonesian snack that is low in protein but high in carbohydrates. Researchers have explored fortifying these crackers with catfish to enhance their nutritional value and increase their protein content. However, the high fat content in catfish can increase overall lipid levels in the crackers, making them more susceptible to oxidation during storage. Using the Arrhenius model, this study aimed to evaluate the kinetics of free fatty acid (FFA) formation in fortified cassava crackers. The enriched product, which included catfish and Centella asiatica leaves, was stored at temperatures of 25°C, 35°C, and 45°C for 28 days in polypropylene packaging that is 0.4 mm thick. FFA levels were measured at 7-day intervals. The results revealed an activation energy (Ea) of 54.01 kJ/mol, indicating that higher storage temperatures accelerate lipid hydrolysis and FFA accumulation. These findings suggested that controlling the storage temperature was crucial to maintaining the quality and stability of fortified cassava crackers.